Penggunaan media games book untuk meningkatkan minat baca pembelajaran ips pada kelas iv sekolah dasar - Ariq Utama; Sri Marmoah; Suharno Suharno (Didaktika Dwija Indria, 2020)
Abstract. Games book learning media is one of the learning media that can help teachers deliver material to students through a game. Games book is a book-shaped media in which there are various games that interest students in reading. The purpose of this study is to prove that the use of media games books can increase reading interest in grade IV students. The type of research is classroom action research conducted in two cycles. Each cycle consists of four steps, namely planning, action, observation and reflection. The subjects of this study were teacher and fourth grade students of Elementary School Djama'atul Ichwan Surakarata. Data collection techniques in this study through observation, interviews, questionnaires, and tests. Data validity testing techniques in this study used triangulation techniques. The results of this study indicate that the reading interest of pre-action students who scored high interest in reading categories was only 29% or 9 students. In cycle I, students who received high interest in reading scores occurred at meeting 1 to 55% or 17 students and meeting 2 to 81% or 25 students. In cycle II there was an increase again in meeting 1 with a score of 87% or 27 students and in meeting 2 to 90% or 28 students. The results showed that the use of game media books could increase the reading interest of Class IV D students at SD Djama'atul Ichwan Surakarta in the academic year 2019/2020.